2017
DOI: 10.1039/c6lc00848h
|View full text |Cite
|
Sign up to set email alerts
|

Controlled production of sub-millimeter liquid core hydrogel capsules for parallelized 3D cell culture

Abstract: Liquid core capsules having a hydrogel membrane are becoming a versatile tool for three-dimensional culture of micro-organisms and mammalian cells. Making sub-millimeter capsules at a high rate, via the breakup of a compound jet in air, opens the way to high-throughput screening applications. However, control of the capsule size monodispersity, especially required for quantitative bioassays, was still lacking. Here, we report how the understanding of the underlying hydrodynamic instabilities that occur during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 60 publications
1
49
1
Order By: Relevance
“…Compound droplets have generally been studied in the context of Newtonian liquid systems [28][29][30][31][32][33][34][35] and only a few studies have considered the effects of viscoelasticity on the deformation and dynamics of compound droplets. [36][37][38] Toose et al 36 developed a boundary element method to model the dynamics of non-Newtonian compound droplets under axisymmetric flow conditions. They identified the dominant breakup mechanism of compound drops in relation to the specific non-Newtonian behavior of the membrane.…”
Section: Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Compound droplets have generally been studied in the context of Newtonian liquid systems [28][29][30][31][32][33][34][35] and only a few studies have considered the effects of viscoelasticity on the deformation and dynamics of compound droplets. [36][37][38] Toose et al 36 developed a boundary element method to model the dynamics of non-Newtonian compound droplets under axisymmetric flow conditions. They identified the dominant breakup mechanism of compound drops in relation to the specific non-Newtonian behavior of the membrane.…”
Section: Articlementioning
confidence: 99%
“…Zhou et al 37 computationally studied the formation of a viscoelastic compound droplet in a flow-focusing geometry but did not consider its dynamics afterward. More recently, Domejean et al 38 demonstrated the controlled production of submillimeter liquid core hydrogel capsules for multiplexed three-dimensional (3D) cell culture.…”
Section: Articlementioning
confidence: 99%
“…Compartmentalization in microbeads provides means to miniaturize and integrate functions based on individual biochemical processes, and to protect microorganisms from the competition with other species in individual ecological niches . Immobilization of living organisms within porous media was previously demonstrated in various soft matter systems . However, the growth of bacterial colonies is hindered by the lack of free volume restricting efficient cell growth and proliferation.…”
mentioning
confidence: 99%
“…For example, Janus microgels formed by using a coflow microfluidic device have been developed for the pairing of hMSCs and human umbilical vein endothelial cells (HUVECs) within one microgels (Figure b), which provide an excellent model for investigating cell‐cell interaction at single cell level . In addition, microfluidics could generate core–shell structured microcapsules for 3D cultivation of cell spheroids within aqueous cores by using flow‐focusing devices . Less shear stress is exerted on the cells during the generation of the microcapsules by microfluidics, which would be beneficial for the preservation of cell functions.…”
Section: Biomedical Applicationsmentioning
confidence: 99%